Cigarette smoking dose-response and suicidal ideation among young people in Nepal: a cross-sectional study - Sathian, Brijesh; Menezes, Ritesh G; Asim, Mohammad; Mekkodathil, Ahammed; Sreedharan, Jayadevan; Banerjee, Indrajit; van Teijlingen, Edwin R; Roy, Bedanta; Subramanya, Supram Hosuru; Kharoshah, Magdy A; et al. (Nepal Journal of Epidemiology, 2020)
Background: Worldwide, tobacco smoking is a major risk factor for morbidity and early mortality among adult population. The present study aimed to find out the association between current smoking and suicidal ideation among young people in Nepal. Materials and Methods: A cross-sectional questionnaire-based survey was carried out among 452 youths from Pokhara, Nepal. The present study included both genders (age 18-24 years) who were smokers as well as non-smokers. Results: Across the study period, 452 participants were identified after matching for age, and sex (226 in the smoking group and 226 in the non-smoking group). The mean age of participants was 21.6±1.2 years and 58.8% were males. The overall rate of suicidal ideation in our cohort was 8.9%. Smokers were slightly more likely to report suicidal ideation than non-smokers (aOR 1.12). The risk of developing suicidal ideation was 3.56 (95% CI 1.26-10.09) times more in individuals who smoked greater than 3.5 cigarettes per week (p=0.01). Conclusion: The rate of suicidal ideation was slightly higher among smokers and a dose-response relationship was identified with the number of cigarettes smoked per week. Being aware of the link between smoking and suicidal ideation may help health care professionals working with young people to address more effectively the issues of mental well-being and thoughts about suicide.